The Emergence of Volleyball Sports and Discovering Students of the Sports of this Sport - Narzulloyevich, Shaymardanov Ravuf (European Journal of Life Safety and Stability (2660-9630), 2021)
This article describes the emergence, development, impact on the health of the sport of volleyball, the development of basic physical qualities of the body increase in functional capacity, range of motor skills and performance borderline, health promotion, recovery process activation, to the external and internal negative effects of the organism has been shown to increase endurance.